2020
DOI: 10.1111/bjhp.12460
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Intuition and Deliberation in Eating Decision‐making: Scale validation and associations with eating behaviour and health

Abstract: Objectives. Two distinct lines of research separately regard either deliberately regulated eating or intuitive eating as most beneficial for health. The present research aims to integrate these seemingly contradictory findings by investigating the relationships between Preference for Intuition and Deliberation in Eating Decision-making (E-PID) and subjective and objective health-related parameters using a newly developed scale. Design. Study 1: online survey; Study 2: cross-sectional community cohort sample. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 91 publications
(131 reference statements)
2
10
1
Order By: Relevance
“…In a similar vein, the E-PID assesses eating decision-making as a trait-like preference that people have, whereas there might also be state-like situation-specific decision-making styles. Although previous research confirmed the notion of decision-making style preferences being rather traits than states (Richetin et al, 2007), at least some people might be able to switch flexibly between the styles, as indicated by some people scoring high on both subscales (Betsch, 2004) (see also König, Sproesser, et al, 2021 for a discussion). Future research therefore needs to examine whether and, if so, under which conditions, situational cues interact with stable interindividual differences in tendencies towards these behaviors to lead to the use of certain decision-making styles.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a similar vein, the E-PID assesses eating decision-making as a trait-like preference that people have, whereas there might also be state-like situation-specific decision-making styles. Although previous research confirmed the notion of decision-making style preferences being rather traits than states (Richetin et al, 2007), at least some people might be able to switch flexibly between the styles, as indicated by some people scoring high on both subscales (Betsch, 2004) (see also König, Sproesser, et al, 2021 for a discussion). Future research therefore needs to examine whether and, if so, under which conditions, situational cues interact with stable interindividual differences in tendencies towards these behaviors to lead to the use of certain decision-making styles.…”
Section: Discussionmentioning
confidence: 94%
“…With regard to the preference for deliberation in eating decision-making, people might not only deliberate on healthy eating, but also on other topics such as price (cf., Renner et al, 2012). However, previous research has shown a considerable relationship between E-PD and choosing food for health reasons (König, Sproesser, et al, 2021), underlines that health concerns play an important role when deliberately deciding to eat. Regarding the preference for intuition in eating decision-making, consuming healthier foods in response to physiological feelings of hunger seems preferable from a purely physical health perspective.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Participants' preference for intuition and deliberation in eating decision-making (E-PID; König et al, 2018König et al, , 2021) was assessed as a potential effect modifier. The measure consists of two subscales: preference for intuition (3 items) and preference for deliberation (4 items).…”
Section: Methodsmentioning
confidence: 99%
“…To date, the question whether self-control-focused or intuitive strategies are most beneficial in promoting healthy eating has mainly been studied in healthy, young samples (e.g., König et al, 2021;Sproesser et al, 2022). We aim to extend this research by comparing the effects of the two strategies for dealing with changes in appetite due to ASD and PTSD on perceived stress, psychological and physical well-being, and diet quality in a real-life setting in Ukranian refugees.…”
Section: Theoretical Backgroundmentioning
confidence: 99%